The German Economy and EU Industrial Tariff Reductions: Partial and CGE Analyses of a Stillborn Millennium Round - Dean Spinanger; Joseph F. Francois; Hans H. Glismann (Kiel Institute of World Economics (IfW), 2000)
The Millennium Round of MTNs, which was stillborn in Seattle, was supposed to have initiated wide-sweeping changes to the world's trading system. This paper deals with the impact on the German economy of some changes that might have been forthcoming from proposed liberalization strategies. It examines sectoral and global strategies with partial and general equilibrium methods. It underlines the advantages of more global strategies, but not only because the gains are significantly larger. The paper concludes that Germany in its own interests should throw its weight in the EU behind wide-sweeping liberalization and that developing countries stand to gain more from global liberalization.
Keywords: C68; F02; F13; F14; L60; O52; 330; Millennium Round; WTO; Multilateral Trade Negotiations (MTN); Trade Liberalization; GTAP; Zolltarif; Industriegüteraußenhandel; Außenhandelsliberalisierung; Wirtschaftspolitische Wirkungsanalyse; Partielles Gleichgewicht; Allgemeines Gleichgewicht; Schätzung; Deutschland